Phytochemical Analysis and Anti-cancer Activity of Rhinacanthus nasutus - Nirmala, Arunachalam; Savitha, Dhanasekar (Asian Journal of Biological and Life Sciences)
Cancer is a condition in which the body cells multiply uncontrollably. It is a deadly disease that develops over the time and it is defined by persistent, aberrant and relatively autonomous cell proliferation as a result of a permanent cellular defect that is handed down to the progeny. It is one of the most common diseases in human population and ongoing identification of new anticancer medicines from natural sources is of great scientific and commercial importance. New, effective and inexpensive anti-cancer treatments are constantly in demand. Traditional medicine is an important and alternative resource for discovering new anti-cancer drugs. One such a medicinal plant Rhinacanthus nasutus (L) (Acanthaceae) comprises three main alkaloids: Rhinacanthin C, Rhinacanthin D and Rhinacanthin N. Rhinacanthin has been considered to have the ability to stop the aberrant cell growth and development. However, no scientific reports on cancer disease has been published. Hence in the present study focused on analysis of phytochemicals in aqueous extract of Rhinacanthus nasutus. The phytochemical analysis of R.nasutus, revealed the presence of alkaloids, phenols, saponins, flavonoids, tannins, steroids and terpenoids except cardiac glycosides. The aqueous extract of Rhinacanthus nasutus possesses a higher concentration of phenolic compounds and flavonoids, according to quantitative phytochemical study. It also possesses the good free radical scavenging activity. Hence the present study, focussed on analysis of phytochemicals and free radical scavenging activity of R.nasutus, will be useful in the synthesis and preparation of new drugs of pharmaceutical importance
Keywords: Antioxidant activity; Leaves extract; Medicinal plants; Phytochemicals; Rhinacanthus nasutus.